Meningkatkan Hasil Belajar Pak Siswa Kelas III Materi Melestarikan Lingkungan Alam Model PBL SDN 17 Tomok TP. 2023/2024 - Herlikia Sinaga (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This research was motivated by the low learning outcomes of students in the material "Preserving the Natural Environment" in class III of SD Negeri 17 Tomok, Simanindo District, Samosir Regency. So, to overcome this problem, researchers used the Problem Based Learning (PBL) learning model. With the aim of improving student learning outcomes by using the Problem Based Learning (PBL) learning model. This research method is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, reflection. The research subjects consisted of 4 class III students. Collection techniques include documentation, observation and tests. The results of this research can be concluded that student learning outcomes in the community element material are Preserving the Natural Environment. Cycle I Meeting 1 was 50% with Newly Developing (BB) criteria. In Cycle I Meeting 2 student learning outcomes increased, namely 74% with the Eligible criteria. In Cycle II, Meeting 1, student learning outcomes increased to 85% with the Cakap criteria. In Cycle II, Meeting 2, student learning outcomes increased to 89% with the Proficient criteria. Thus, it can be concluded that using the Problem Based Learning (PBL) learning model can improve student learning outcomes in the Material of Preserving the Natural Environment in class III of SD Negeri 17 Tomok.